Factors contribute to high prevalence of non-communicable disease among university students in Malaysia / Erni Tanius … [et al.] - Tanius, Erni; Tuan Othman, Sharifah Izwan; Mohd Kasim, Che Manisah; Alias, Rozila (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Non-communicable diseases (NCD) among young people are worsening in Malaysia and globally. The prevalence is increasing, and it is directly influence their future life, namely employment. As it becomes trend that employers are reluctantly hiring of noncommunicable diseases carriers. Hence, the scope of this research focuses on the factors that cause the high prevalence of non-communicable diseases among university student; they are Body Mass Index (BMI) and mental health. The variables are designed based on the existing and related literature by using questionnaire. The questionnaire has been distributed to 226 university students in Shah Alam, Selangor, Malaysia. Descriptive Statistics, ANAVA, and T- Test are used to analyses the data. The finding also showed that almost quarters of respondents were overweight, mildly obese and extremely obese. The worrying result indicated that the depression and anxiety rate are high.